Submerged Floating Tunnel: a solution proposal for the problems of communication and development of the Baja California Peninsula in the northwest of Mexico - Panduro Noriega, Joaquín Omar (My University, 2013)
Submerged Floating Tunnel Gulf of California Safety in Tunnels
Keywords: Submerged Floating Tunnel Gulf of California Safety in Tunnels